(untitled) (The Eurasia Proceedings of Educational and Social Sciences, 2016)
We created citizen science project called “nuclear e-cology”, and proposed it to high school teachers. Its main purpose was, in particular, to introduce the modern physics and science, in general, to afterhours school activities and eventually to modify high school curricula. We also put a special attention to the teamwork and the general scientific methods. Groups of students initially started the serious scientific work and some of them finished the study in the 2014/15 school year and we found results of their activity of the real physical value. We shortly present some of them here. We discuss here also some educational aspects of the project based on interviews and opinions of teacher involved in the project. We believe that the further work could be fruitful and successful from the point of view of students and teachers.